Conflict of Rules in Labor Law: Challenges of Recodification - Shumylo, Mykhailo (Problems of legality, 2026)
The relevance of scientific research is determined by the processes of recodification of labor and civil legislation. Currently, drafts of the Labor and Civil Codes have been registered in parliament, and both drafts contain provisions that define the legal regulation of labor relations with a foreign element. Given the interdisciplinary nature of conflict-of-law rules in labor law, their place in the national legal system needs to be scientifically justified. The article describes the evolutionary path of conflict-of-law rules in general in selected European Union countries. Three stages are proposed: (1) the pre-unification period, (2) the Rome Convention (1980), (3) the Regulation (Rome I) (2008). This shows the long road to a single document that now regulates the rules for applying conflict-of-law rules in the form of Regulation (EC) No 593/2008 of the European Parliament and of the Council on the law applicable to contractual obligations (Rome I). In addition, it is emphasized that in the event of a dispute, the issue of determining jurisdiction is governed by Regulation (EU) No. 1215/2012 of the European Parliament and of the Council on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters. The study also focuses on the experience of some European Union countries in incorporating the rules of private international labor law into their national legislation. For example, the labor codes of Lithuania and Latvia contain separate chapters that regulate labor relations with a foreign element. The study traces the evolution of conflict-of-law rules in labor legislation and their subsequent removal from the Labor Code and transfer to a special Law of Ukraine "On International Private Law." The article presents and analyzes the provisions of the draft Labor Code, which return conflict-of-law rules in labor law to labor legislation. The article is supplemented by a novum that defines the law applicable to Ukrainian citizens working in international organizations governed by the internal law of these organizations. It also emphasizes the fact that, in addition to these provisions, the draft Labor Code implements EU Directive 96/71/EC of December 16, 1996, on the posting of workers in the framework of the provision of services, which demonstrates the comprehensive nature of the recodification of labor legislation. The conclusions emphasize the advisability of enshrining conflict-of-law rules in labor law specifically in the Labor Code, which will facilitate comprehensive recodification and ease of use.